Psychological characteristics of patients with myotonic dystrophy type 1. (11th December 2014) - Bertrand, J. A.; Jean, S.; Laberge, L.; Gagnon, C.; Mathieu, J.; Gagnon, J. F.; Richer, L.
<x xml:space="preserve">Abstract</x> Objectives Myotonic dystrophy type 1 (DM1) is the most common adult‐onset muscular dystrophy. It is associated with motor symptoms but patients also display non‐motor symptoms such as particular personality traits. Studies have reported mixed results about personality characteristics which may be attributable to small sample sizes, different disease severity of groups studied, and use of different questionnaires or method. This study aimed to describe the psychological characteristics of a large cohort of patients with DM1, to characterize those at risk of developing a psychiatric disorder, and to compare characteristics between two DM1 phenotypes, a mild and more severe adult‐onset phenotype. Methods Two hundred patients with DM1 (152 adult‐onset; 48 mild) were asked to complete questionnaires assessing personality traits, psychological symptoms, self‐esteem, and suicidal risk. Neurological and neuropsychological assessments were performed to compare personality characteristics to clinical and cognitive measures. Results Patients with DM1 globally showed personality traits and psychological symptoms in the average range compared to normative data, with normal levels of self‐esteem and suicidal ideation. However, 27% of patients were found to be at high risk of developing a psychiatric disorder. Moreover, psychological traits differed across phenotypes, with the most severe phenotype tending to show more severe psychological symptoms. The presence of higher phobic anxiety and lower self‐esteem was associated with lower education, a higher number of CTG repeats, more severe muscular impairment, and lower cognitive functioning (P < 0.001). Conclusions Different phenotypes should thus be taken into account in clinical settings for individual management of patients and optimizing therapeutic success.